The Effect of Local Intraoperative Steroid Administration on the Rate of Postoperative Dysphagia Following ACDF: A Study of 245, 754 Patients. Issue 13 (July 2016) - Cancienne, Jourdan M.; Werner, Brian C.; Loeb, Alex E.; Yang, Scott S.; Hassanzadeh, Hamid; Singla, Anuj; Shen, Frank H.; Shimer, Adam L.
Abstract : Study Design: A retrospective database analysis. Objective: The aim of this study is to compare rates of postoperative dysphagia, length of stay, infection, and wound complications following short and long anterior cervical discectomy and fusion (ACDF) in patients who received local intraoperative steroids and those who did not. Summary of Background Data: Only one prior small institutional study has investigated the application of local steroids at the time of ACDF to decrease postoperative dysphagia. Methods: A large administrative database was utilized to compare rates of postoperative dysphagia, length of stay, and infectious complications within 90 days in patients who received local steroid following short (1–2 level) and long (3 or more level) ACDF and control groups who did not. Nonobtainable information within the database included type of steroid, application technique, outcome data, and incidence of miscoding and noncoding by physicians. Odds ratios (ORs), 95% confidence intervals (95% CIs) and P values were then calculated using SPSS. Results: The incidence of dysphagia was significantly lower (9.0% vs . 14.6%, P  = 0.005) in patients who received local steroid in the long ACDF group (n = 322) than a control group who did not (n = 45, 432). This was not observed ( P  = 0.198) in the short ACDF group who received steroid (n = 1770) compared with a control group who did not (n = 198, 230). The mean difference in length of stay was 1 day less for patients who received local steroid in both the short and long ACDF groups ( P  < 0.0001). The combined rate of postoperative infection and wound complications was not significantly different between steroid and control groups ( P  = 0.717). Conclusion: This analysis of a large administrative database suggests that local intraoperative steroid is associated with a significantly reduced rate of postoperative dysphagia after long ACDF and reduced average length of stay following both long and short ACDF without any increase in the rate of postoperative infection or wound complication. Level of Evidence: 3